2022
DOI: 10.1002/mc.23481
|View full text |Cite
|
Sign up to set email alerts
|

POR overexpression induces tamoxifen‐resistance in breast cancer through the STAT1/c‐Myc pathway

Abstract: Breast cancer is the most common cancer in women worldwide. Although tamoxifen (TAM), a selective estrogen receptor (ER) modulator, is widely used to treat ER‐positive breast cancers, resistance to TAM remains a major clinical problem. NADPH‐dependent cytochrome P450 reductase (POR) is known to participate in drug metabolism and steroid metabolism. Recent studies showed that high POR expression was correlated with poor outcomes in triple‐negative breast cancer (TNBC), and POR might be a prognostic biomarker in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A previous study has identified that suggest that increased STAT1 signaling is important in endocrine resistance and that STAT inhibitors may represent potential therapies in endocrine-resistant breast cancer (Huang et al, 2014;Chen et al, 2023). STAT1/c-Myc pathway is involved in PORinduced TAM-resistant breast cancer (Chen et al, 2023). The present study reveals a possible tamoxifen-resistant mechanism by which hsa_circ_0086735 may sponge miR-1296-5p, indirectly moderating STAT1 and contributing to tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A previous study has identified that suggest that increased STAT1 signaling is important in endocrine resistance and that STAT inhibitors may represent potential therapies in endocrine-resistant breast cancer (Huang et al, 2014;Chen et al, 2023). STAT1/c-Myc pathway is involved in PORinduced TAM-resistant breast cancer (Chen et al, 2023). The present study reveals a possible tamoxifen-resistant mechanism by which hsa_circ_0086735 may sponge miR-1296-5p, indirectly moderating STAT1 and contributing to tamoxifen resistance.…”
Section: Discussionmentioning
confidence: 59%
“…Depletion of STAT1 can decrease levels of ERα protein and cell proliferation in tamoxifen-resistant cell line LCC2 (Hou et al, 2018). A previous study has identified that suggest that increased STAT1 signaling is important in endocrine resistance and that STAT inhibitors may represent potential therapies in endocrine-resistant breast cancer (Huang et al, 2014;Chen et al, 2023). STAT1/c-Myc pathway is involved in PORinduced TAM-resistant breast cancer (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 98%